Identity, transcendence and the true self: Insights from psychology and contemplative spirituality - Haynes, Carter (HTS teologiese studies, 2016)
This article investigates the intersection of psychology and spirituality as seen through the works of Thomas Merton, Carl Jung, Fritz Kunkel and Viktor Frankl. The themes of spirituality contextualised in human identity, psychological and spiritual transcendence, and the true self versus false self metaphor are traced through the works of all four thinkers. Epistemological flexibility and holistic thinking and being are suggested as methods for transforming interdisciplinary practitioners, such as pastoral counsellors, spiritual directors and spiritually oriented psychotherapists, in order that they can offer care in a less bifurcated and more integrated way. Practical applications, including a vignette and specific recommendations for broadening and deepening personal and professional integrative practice, are offered.